2017
DOI: 10.1108/jsfe-05-2017-0033
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical modeling for predicting the axial restraint forces and rotations of steel top and seat angle connections at elevated temperatures

Abstract: Purpose This paper aims at developing a mechanical-based model for predicting the thermally induced axial forces and rotation of steel top and seat angles connections with and without web angles subjected to elevated temperatures due to fire. Finite element (FE) simulations and experimental results are used to develop the mechanical model. Design/methodology/approach The model incorporates the overall connection and column-beam rotation of key component elements, and includes nonlinear behavior of bolts and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In this type of contact model, the surfaces are allowed to slide across each other in the tangential direction. According to the previous studies, a range of 0.25–0.44 is considered for the friction coefficient of steel-steel contacts at high temperatures (El Kalash and Hantouche, 2017; Sarraj et al ., 2007; Haremza et al ., 2016; Pakala et al ., 2012; Zahmatkesh et al ., 2019; Eslami et al ., 2018; Dai et al ., 2010; Chen and Wang, 2012; Elsawaf and Wang, 2013; Wang and Wang, 2013; Kodur et al ., 2013; Xie et al ., 2018; Li et al ., 2020; Kalogeropoulos et al ., 2012; Qiang et al ., 2014). So, the “penalty” method and Coulomb's frictional law with a constant friction coefficient of 0.3 were applied to the model to obtain the frictional forces between the angels, column and beam.…”
Section: Finite Element Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In this type of contact model, the surfaces are allowed to slide across each other in the tangential direction. According to the previous studies, a range of 0.25–0.44 is considered for the friction coefficient of steel-steel contacts at high temperatures (El Kalash and Hantouche, 2017; Sarraj et al ., 2007; Haremza et al ., 2016; Pakala et al ., 2012; Zahmatkesh et al ., 2019; Eslami et al ., 2018; Dai et al ., 2010; Chen and Wang, 2012; Elsawaf and Wang, 2013; Wang and Wang, 2013; Kodur et al ., 2013; Xie et al ., 2018; Li et al ., 2020; Kalogeropoulos et al ., 2012; Qiang et al ., 2014). So, the “penalty” method and Coulomb's frictional law with a constant friction coefficient of 0.3 were applied to the model to obtain the frictional forces between the angels, column and beam.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…(2016) showed that the gap distance, initial cooling temperature, load ratio and position of the double angle with respect to the beam neutral axis are the main factors impacting the behavior of bolted double angle connections in fire conditions. Using FE simulations and experimental results (El Kalash and Hantouche, 2017) developed a mechanical-based model for predicting the thermally induced axial forces and rotation of steel bolted top and seat angles connections with and without web angles subjected to fire. The proposed model consisted of multi-linear and nonlinear springs that predict each component stiffness, strength and rotation.…”
Section: Introductionmentioning
confidence: 99%
“…There are also many papers on the determination of the behaviour of bolted connections under fire conditions [12,13,19,21,[37][38][39] and several on the behaviour of bolted connections at reduced temperatures [29,47,50] using FEM.…”
Section: Introductionmentioning
confidence: 99%
“…Rational models were developed to predict the thermal response of other types of connections in bare steel beams, such as flush endplate (Jones, 1997; El Ghor and Hantouche, 2017), shear endplate (Hu et al , 2009a, 2009b; Hantouche and Sleiman, 2017), double angle (Hantouche et al , 2018) and top and seat angle connections (El Kalash and Hantouche, 2017). For instance, Hu et al (2009a, 2009b) proposed a rational model for shear end plate connections to predict the force-rotation behavior of the connection at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%